Evaluation of the work ability of primary health care professionals: A cross-sectional study (Research, Society and Development, 2021)
The objective was to assess the functional capacity of professionals in the Family Health Strategy through the Work Ability Index. This is a cross-sectional, exploratory, descriptive study, used as an instrument of analysis, using the Work Ability Index scale. The survey was conducted in nine Primary Health Care units in Rio de Janeiro, Brazil, from July to November 2018, with 88 professionals from multidisciplinary teams. Descriptive statistics were used for all variables and coefficient of variation calculation for quantitative variables. Most participants are women (80.7%), with an average age of 43 years (40.6%), currently working in just one job (85.2%) and with a weekly workload of 40 hours (87.5%) and having been working in the current workplace for just one year (30.7%). They felt demanded to work physically and mentally (95.5%) professionals. The most prevalent comorbidities were: hypertension and back injuries, both with (26.1%) participants. The research also showed that illnesses related to back injuries (p-value=0.013) and mild depression (p-value=0.002) directly influenced work ability, and reflected in lower scores, which were confirmed by the statistical test of Mann Whitney. It was concluded that musculoskeletal pain and mild depression decreased the work capacity of primary care health professionals. This study seeks to contribute to research on the theme of workers' health, in monitoring the functional capacity of health professionals, aiming at the prevention of occupational diseases and the healthy aging process.